Modelling of Solar Power Generation in Malaysia: A Time Series Analysis - Nurul Ain Najwa Zainal Abidin; Noor'Adilah Ibrahim; Neelabja Chatterjee (Akademia Baru Publishing, 2026)
Non-Indexed Publication